2020
DOI: 10.3389/fnins.2020.598888
|View full text |Cite
|
Sign up to set email alerts
|

On the Organization of the Locomotor CPG: Insights From Split-Belt Locomotion and Mathematical Modeling

Abstract: Rhythmic limb movements during locomotion are controlled by central pattern generator (CPG) circuits located in the spinal cord. It is considered that these circuits are composed of individual rhythm generators (RGs) for each limb interacting with each other through multiple commissural and long propriospinal circuits. The organization and operation of each RG are not fully understood, and different competing theories exist about interactions between its flexor and extensor components, as well as about leftrig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 64 publications
(182 reference statements)
4
15
0
Order By: Relevance
“…The neurons in the F and E half-centers incorporate a slowly inactivating persistent sodium current (INaP) and are connected by excitatory synaptic connections that allow them to generate synchronized populational bursting activity in a certain range of an external brainstem drive. As in our previous models (Rybak et al, 2013(Rybak et al, , 2015Molkov et al, 2015;Shevtsova et al, 2015;Danner et al, 2016Danner et al, , 2017Danner et al, , 2019Shevtsova and Rybak, 2016;Ausborn et al, 2019Ausborn et al, , 2021Latash et al, 2020), only the F half-centers operate in a bursting regime and generate intrinsically rhythmic activity, while the E half-centers receive a relatively high tonic drive and are tonically active if uncoupled. The E half-centers generate rhythmic activity only due to inhibition from the intrinsically oscillating F half-centers.…”
Section: Modeling the Organization Of Spinal Circuits Involved In Control Of Locomotionsupporting
confidence: 57%
See 2 more Smart Citations
“…The neurons in the F and E half-centers incorporate a slowly inactivating persistent sodium current (INaP) and are connected by excitatory synaptic connections that allow them to generate synchronized populational bursting activity in a certain range of an external brainstem drive. As in our previous models (Rybak et al, 2013(Rybak et al, , 2015Molkov et al, 2015;Shevtsova et al, 2015;Danner et al, 2016Danner et al, , 2017Danner et al, , 2019Shevtsova and Rybak, 2016;Ausborn et al, 2019Ausborn et al, , 2021Latash et al, 2020), only the F half-centers operate in a bursting regime and generate intrinsically rhythmic activity, while the E half-centers receive a relatively high tonic drive and are tonically active if uncoupled. The E half-centers generate rhythmic activity only due to inhibition from the intrinsically oscillating F half-centers.…”
Section: Modeling the Organization Of Spinal Circuits Involved In Control Of Locomotionsupporting
confidence: 57%
“…The basic architecture of the model has been developed for several years to be able to reproduce experimental data from multiple independent experimental studies (Rybak et al, 2013(Rybak et al, , 2015Molkov et al, 2015;Shevtsova et al, 2015;Danner et al, 2016Danner et al, , 2017Danner et al, , 2019Shevtsova and Rybak, 2016;Ausborn et al, 2019Ausborn et al, , 2021Latash et al, 2020) and was extended here to incorporate the results of experimental studies described above. The detailed schematic of the model is shown in Figure 7 and its major components are shown in Figure 8 and described below.…”
Section: Modeling the Organization Of Spinal Circuits Involved In Control Of Locomotionmentioning
confidence: 99%
See 1 more Smart Citation
“…We followed ARRIVE guidelines for animal studies (Percie du Sert et al, 2020). In our effort to reduce the number of animals used in research, we used these cats in other studies to answer different scientific questions (Latash et al, 2020;Harnie et al, 2019Harnie et al, , 2021Merlet et al, 2020Merlet et al, , 2021.…”
Section: Animals and Ethical Informationmentioning
confidence: 99%
“…Thus, state-dependent modulation of the neuronal components of the rhythm generators could set different operating regimes appropriate for the locomotor task at hand. For example, Latash et al [125] showed that a model implementing a transition from a flexor-dominant regime at low locomotor frequencies to a classical half-center regime at high frequencies can explain the left-right asymmetries of split-belt locomotion in spinal cats [126,127].…”
Section: Computational Models Based On Classical Experimental Studiesmentioning
confidence: 99%